Effects of Seeding Density on Growth Attributes of Broadleaf Mustard in Nursery Bed - Niraula, Nisha; Timilsina, Anil (International Journal of Applied Sciences and Biotechnology, 2020)
The productivity of crops is highly affected by the seedling quality, which is governed by seeding density in the nursery. So, an experiment was conducted to explore the effect of seedling spacing in the growth attributes of Broad Leaf Mustard cv. “Marpha Chauda Paate” at IAAS, Lamjung Campus, during Oct 2018. Four spacing treatments viz 0.5 cm × 1 cm, 1 cm × 1 cm, 1.5 cm ×1.5 cm and 2 cm × 2 cm were arranged in RCB Design with 5 replications. Observation of seedling height, leaf area, leaf number, shoot & root fresh weights, shoot dry matter, and dry matter percentage from twenty-three days old seedlings were recorded. The total leaf area was estimated using the Image-J package. Data were tabulated in MS Excel and analyzed by Gen Stat. Treatments differed significantly in seedling height, shoot and root fresh weight, leaf area, root length, and shoot dry weight, while the number of leaves and dry matter percentage did not differ statistically. Maximum shoot fresh weight (1.09 g), shoot dry weight (0.11 g), leaf area (48.24 cm2), root length (4.89 cm), root fresh weight (0.03 g) per plant and shoot dry matter percentage (9.24%) were found in widest spacing (2 cm × 2 cm). However, seedling height was recorded higher in closer spacing. Therefore, the study of the overall characteristics asserted that the seed spaced at 2 cm × 2 cm produced superior seedling over all other spacings. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 65-70